Anti-CD4-targeted gold nanoparticles induce specific contrast enhancement of peripheral lymph nodes in X-ray computed tomography of live mice - Eck, Wolfgang; Nicholson, Anthony I.; Zentgraf, Hanswalter; Semmler, Wolfhard; Bartling, Sönke (Nano letters, 2010)
Antibody-conjugated gold nanoparticles have been applied as a biologically targeted contrast agent in live mice for one of the most widely used medical imaging methods, X-ray computed tomography. Such nanoprobes directed toward the CD4 receptor lead to distinctly enhanced X-ray contrast of peripheral lymph nodes. This study demonstrates the general feasibility of biologically specific X-ray imaging in living animals and discusses basic requirements for the use of nanoparticles as a targeted X-ray contrast agent.